Memahami Hambatan Keterbukaan Diri Klien Rehabilitasi Narkotika: Perspektif Teori Atribusi Staf Rehabilitasi (Understanding Barriers to Self-Disclosure among Drug Rehabilitation Clients: An Attribution Theory Perspective of Rehabilitation Staff) - Qodriatul Fitri, Laila; Darwati, Yuli (Happiness: Journal of Psychology and Islamic Science, 2026)
This study aims to analyze rehabilitation staff attributions regarding barriers to client self-disclosure during the drug rehabilitation process at the National Narcotics Agency (BNN) of Kediri City. Self-disclosure is a crucial element in addiction counseling because it serves as the basis for assessing clients’ psychological conditions, substance-use history, and planning appropriate interventions. However, clients often experience difficulties in disclosing personal information, such as withholding important information, providing inaccurate responses, and avoiding counseling sessions. These barriers occur among both compulsory and voluntary clients, although they manifest in different forms. This study employed a descriptive qualitative approach involving two rehabilitation staff members selected through purposive sampling. Data were collected through in-depth interviews and observations of staff–client interactions. Data analysis consisted of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that rehabilitation staff construct both internal and external attributions in understanding barriers to client self-disclosure. Internal attributions relate to clients’ motivation, readiness for recovery, and coping abilities, whereas external attributions involve social stigma, environmental pressures, concerns regarding legal status, and unstable psychological conditions. These attributions influence the support strategies employed, including humanistic approaches, creating informal counseling settings, maintaining client privacy, and coordinating across services. The findings highlight the important role of staff attributions in fostering effective therapeutic relationships and supporting successful rehabilitation outcomes.